Choledochal cyst and aberrant biliary configuration along with situs inversus totalis: A case report - Eng, David Yeow Gan; Dinesh Alagoo; Kheng, Hooi Chan; Xin, Rebecca Yee Choi; Harivinthan Sellappan; Mohd Sharifudin Sharif; Firdaus Hayati (Pan African Medical Journal, 2021)
Situs inversus totalis is the complete transpositioning of thoracoabdominal viscera into a mirror image of the normal configuration. Choledochal cyst is the congenital cystic dilation of the biliary tract. Both these conditions coexisting in a patient is extremely rare. We hereby present a case of type IC choledochal cyst in a patient with situs inversus totalis presenting with biliary sepsis secondary to choledocholithiasis. Also detailed are the management and operative strategies employed to deal with this rare entity.